Adverse Effects of Ultraviolet Radiation on Growth, Behavior, Skin Condition, Physiology, and Immune Function in Gilthead Seabream (Sparus aurata) - Alves, Ricardo N.; Mahamed, Asaad H.; Alarcon, Jorge F.; Al Suwailem, Abdulaziz; Agustí, Susana (Frontiers in Marine Science, 2020)
Ultraviolet B (UVB) radiation has recently been recognized as a major stressor for marine vertebrates, particularly fish confined to aquaculture cages. Here, we investigate the harmful effects of UVB radiation on gilthead seabream (Sparus aurata), which is a widely cultured species. We exposed juveniles to three UVB conditions (UVB-H - high UVB, 12 kJ m-2 d-1; UVB-M - moderate UVB, 6 kJ m-2 d-1; UVB-L - low UVB, 2.4 kJ m-2 d-1) that are representative of natural underwater UVB levels throughout the water column in the Red Sea. We used one experimental treatment without UVB exposure as a control. We evaluated the adverse effects of UVB after short- (10 days) and long-term (43 days) exposure. The results indicated that short- and long-term exposure to UVB retarded growth and decreased survival rates. UVB exposure resulted in behavioral changes, mainly in UVB-H and UVB-M exposed fish. Swimming activity was reduced; most of the fish tried to avoid exposure and showed a stationary behavior with slow caudal and dorsal fins movements (UVB-H), or a slow displacement behavior (UVB-M). Moreover, we observed a reduction in appetite, reflected by a remarkable increase in the time required to consume the food. Lesions on the skin occurred in the three UVB treatments, and the incidence and severity increased under long-term UVB exposure. We also observed physiological changes, including a decrease in total protein and total cholesterol concentrations (all UVB treatments). We detected a potential suppression of the innate immune system (reduction of total anti-protease and total peroxidase activities) (UVB-M, UVB-L). Our results suggest that exposure to solar underwater UVB radiation levels has the potential to interfere and affect the health of S. aurata. Indeed, aquaculture fish species growing at locations where water transparency and UVB incidence is as high as the Mediterranean in summer, and the Red Sea year-round, may be affected, and their welfare, resistance to pathogens, and survival may be compromised. Strategies should be considered to mitigate the adverse effects of UVB exposure, such as deeper and more-shaded cages, or the development of functional foods.